Pemberdayaan Ekonomi Masyarakat Dusun Thekelan melalui Pemanfaatan Limbah Organik menjadi Eco-Enzyme - Ekaviana, Dessy; Trisni Suryarini; Hasan Mukhibad; Nur Anita; Atik Ul Mussanadah; Andhina Putri Keriyanti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Household organic waste production in Thekelan Hamlet has increased along with population density and agricultural activities, potentially having negative impacts on the environment and health. However, this waste actually has the potential to be processed into environmentally friendly products with economic value, one of which is eco-enzymes. This community service activity aims to increase community awareness and skills in processing organic waste into eco-enzymes through a participatory approach, technical training, and live demonstrations. The main partners in this activity are housewives and village environmental cadres, who are the main targets for introducing organic waste processing techniques. During the implementation, participants were trained on the benefits and how to produce eco-enzymes independently. This activity not only provided an understanding of the eco-enzyme production process but also motivated participants to produce eco-enzymes independently at home. The results of this activity showed a significant increase in understanding of the benefits of eco-enzymes as an environmentally friendly product, which can be used as a natural cleaner and organic fertilizer. In addition, participants also began to demonstrate the initiative to produce eco-enzymes independently, which has the potential to reduce household organic waste and increase economic value through the utilization of this product. The findings from this activity demonstrate that community-based waste management can not only be an environmentally friendly solution but also has high economic value. This empowerment model can serve as a sustainable model and be implemented in other areas, providing extensive benefits to the environment and the local economy. Furthermore, this activity introduced the concept of sustainable waste management to the community, providing them not only with new knowledge about organic waste processing but also with the opportunity to apply these techniques in their daily lives.